Predictive value of postoperative prognostic nutritional index trajectory for mortality outcomes after off-pump coronary artery bypass surgery: a retrospective cohort study - Bae, Myung Il; Shim, Jae-Kwang; Lee, Hye Sun; Jeon, Soyoung; Kwak, Young-Lan (Frontiers in Nutrition, 2025)
BackgroundThe prognostic nutritional index (PNI) has been widely used as a nutritional metric in patients undergoing cardiac surgery because of its ability to incorporate both nutritional and inflammatory statuses. However, while preoperative PNI is well-known for its predictability of outcomes after coronary artery bypass grafting (CABG), the prognostic value of postoperative PNI has rarely been evaluated. This study investigated the changes in postoperative PNI values following off-pump coronary artery bypass (OPCAB) surgery using a trajectory analysis method and analyzed its influence on mortality outcomes.MethodsWe retrospectively analyzed the data of 983 patients who underwent OPCAB surgery. PNI values from postoperative days 1, 2, 3, and 1 month was analyzed using the trajectory method, and patients were grouped based on the patterns of change in PNI values. The 1-year and overall mortality rates were compared between PNI trajectory groups. Additionally, multivariable logistic regression analysis was performed to identify independent risk factors for 1-year all-cause mortality, and multivariable Cox regression analysis was conducted for overall mortality.ResultsThe trajectory analysis categorized patients into two groups: the “PNI-improved group,” characterized by a sharp increase in PNI values after surgery, and the “PNI-fixed group,” which exhibited minimal changes in PNI values. The PNI-improved group had significantly lower 1-year mortality (1.1% vs. 9.5%, p < 0.001) and overall mortality (16.9% vs. 42.4%, p < 0.001) compared to the PNI-fixed group. Furthermore, the multivariable regression analysis indicated that the PNI trajectory pattern was an independent predictor of 1-year mortality (odds ratio: 7.931, 95% confidence interval [CI]: 3.117–20.180, p < 0.001) and overall mortality (hazard ratio: 2.120, 95% CI: 1.579–2.845, p < 0.001).ConclusionsPatients who exhibited a significant increase in PNI values during the month following OPCAB surgery experienced significantly lower 1-year and overall mortality rates than those with minimal changes in postoperative PNI values. The PNI recovery pattern was identified as an independent predictor of both 1-year and overall mortality after adjusting confounding factors. Recognizing the recovery patterns of postoperative PNI values after OPCAB surgery may be valuable for screening patients at high risk for mortality.